Exploration of the Relationship between Classroom Display Management and Elementary School Students' Learning Achievement in Various Learning Conditions - Yampap, Umar (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to explore the relationship between classroom display management and the achievement of learning achievement of elementary school students under various learning conditions. Classroom display management includes the management of visual elements such as educational posters, concept maps, student works, as well as interactive media designed to create a conducive and interesting learning environment. With a qualitative descriptive approach, this study involves observation, interviews, and data analysis on students and teachers in elementary schools who apply classroom display strategies. The results of the study show that well-managed classroom displays contribute significantly to increasing learning motivation, active student engagement, and material comprehension. In addition, the effectiveness of classroom display management varies based on learning conditions, both in face-to-face learning, blended learning, and online learning. This research emphasizes that classroom displays are not only decorative elements, but also pedagogical tools that are able to improve the quality of learning and student learning achievement.